Pengaruh Penerapan Sapta Pesona Terhadap Kepuasan Wisatawan di Situ Bagendit - Siti Anis Khoerul Nisa Sunerlan; Apay Safari; Anti Riyanti (Manajemen dan Pariwisata, 2023)
This research was conducted at Situ Bagendit which is located on Jl. Kyai Haji Hasan Arif, Sukamukti Village, Banyuresmi District, Garut Regency, with the title the influence of the application of Sapta Pesona on tourist satisfaction. The purpose of this study was to describe the application of Sapta Pesona, the description of tourist satisfaction, and the effect of Sapta Pesona application on tourist satisfaction in Situ Bagendit. The method used in this research is a simple linear regression with a descriptive and verificative analysis approach. The research sampel used was 100 tourist respondents who had visited Situ Bagendit. Descriptive research results show that sapta pesona is in a good category with an average value of 76.3% and tourist satisfaction is in a good category with an average value of 77.2%. While the definitive analysis shows a total effect of 71.10% and the remaining 28.90% is another variable outside of this study. This study also showed positive and significant results.